Genetic Variation of Butternut Squash (Cucurbita moschata Duchesne) based on Inter-Simple Sequence Repeat - Nabila Rizki Ananda Putri; Prima Sekti Kusnanda; Bunga Finovel Angellya; Dian Sartika; Purnomo Purnomo; Budi Setiadi Daryono (Journal of Tropical Biodiversity and Biotechnology, 2023)
Butternut squash (Cucurbita moschata) is a Cucurbitaceae plant that has been widely cultivated in Indonesia. Butternut squash is known to have various cultivars. A new cultivar introduced by the Faculty of Biology UGM is named ‘Citra Laga’ which is expected to be able to compete with the imported cultivars. The number of cultivars within a species may indicate genetic variation. This research was conducted to observe genetic variation and the phenetic relationship between ‘Citra Laga’ and the imported butternut squash cultivars based on the molecular marker ISSR. The ISSR analysis between ‘Citra Laga’ and the imported cultivars showed an average low polymorphism rate by 18.61% with a high similarity percentage of 83.7%. Thus, it can be said that the genetic variation is low and ‘Citra Laga’ is not genetically much different from the imported cultivars.